Digital Branding Adaptation in the Instagram Communication of ‘Aisyiyah’s Majelis Tabligh and Ketarjihan - Kholifatul Fauziah (Journal of Management and Social Sciences, 2026)
This study analyzes the adaptation of digital branding practices carried out by the Pimpinan Pusat ‘Aisyiyah Majelis Tabligh dan Ketarjihan (PPA MTK) through its Instagram account @ppa.majelistablighketarjihan. The study employed a qualitative descriptive approach using content analysis, documentation, and limited participatory observation. Data were collected from the Instagram accounts @aisyiyahpusat and @ppa.majelistablighketarjihan, organizational documents, workshop materials, and digital tabligh guidelines. The findings show that PPA MTK adapted several branding elements from the central organizational account, including visual identity, hashtags, audience greetings, and communication planning structures. However, the adaptation process did not emerge through formal organizational obligations but developed collaboratively through workshops and shared organizational identity. The study also found differences in communication orientation and content pillar structures between the two accounts. While @aisyiyahpusat emphasized broader institutional communication themes, @ppa.majelistablighketarjihan focused more on digital tabligh communication. These findings indicate that branding adaptation within faith-based women organizations may develop through organizational interaction and functional communication differentiation rather than rigid communication standardization.